A preparation method of a microbially regulated and composite metal oxide photocatalytic material and its application in photocatalytic reduction of carbon dioxide reaction
Through microbial regulation and composite of nitrogen and phosphorus co-doped carbon materials and metal oxides, the problem of low utilization efficiency of visible light and electron hole recombination in the existing photocatalytic system is solved, and efficient carbon dioxide conversion and goal are achieved Product yield.
Patent Information
- Application Number
- CN202410847180.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-06-27
AI Technical Summary
When the existing photocatalytic system uses solar energy to drive carbon dioxide to convert it into high value-added products, it is limited by the low utilization efficiency of visible light and the easy recombination of photogenerated electron holes, resulting in a low carbon dioxide conversion rate and target product yield.
Using the preparation method of microbial regulation and composite metal oxide, nitrogen and phosphorus co-doped carbon materials are prepared through the "one-pot method" green method to modify metal semiconductor materials to form heterojunctions to promote the separation of electron holes and high efficiency. Transfer.
The photocatalytic performance and stability of the photocatalytic material are improved, and the yield of the target product is enhanced, which is specifically manifested as the CH4 yield is 1.5 μmol g-1h-1 and the CO yield is 7.3 μmol g-1h-1.
Smart Images

Figure CN118744008B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalytic synthetic materials, and specifically relates to a preparation method of a microbially regulated and composite metal oxide photocatalytic material and its application in a photocatalytic reduction of carbon dioxide reaction. Background Art
[0002] The massive consumption of fossil fuels (such as coal, oil, natural gas, etc.) not only causes an energy crisis, but also the emission of greenhouse gas carbon dioxide far exceeds the processing capacity of nature, which will bring many environmental and ecological problems.
[0003] To this end, developing clean and renewable energy, improving the energy structure, reducing carbon dioxide emissions and reducing the concentration of carbon dioxide in the atmosphere through carbon dioxide capture and conversion technology have become the two main directions. Among them, developing an efficient photocatalytic system and using solar energy to drive carbon dioxide into high-value-added energy and chemical products is a very promising solution. At present, many metal oxides have been applied to this catalytic system, but due to the low efficiency of visible light utilization, the easy recombination of photogenerated electrons and holes leads to a low conversion rate of carbon dioxide, and the yield of target products (methane, CO, methanol, etc.) is low.
[0004] Studies have shown that carbon materials have high light absorption and electron transmission capabilities. Carbon materials have many advantages in modified metal oxides, such as increasing specific surface area, increasing the adsorption capacity of substrates, enhancing light absorption capacity, and increasing electron transmission capacity. Chinese Patent (202110057935.3) obtains a lower band gap value than pure CdS by compounding CdS with MOF-808 and RGO, thereby increasing the effective catalytic activity area of CdS, shortening the migration distance of photogenerated carriers, and greatly accelerating the carrier migration rate, thereby improving the quantum utilization efficiency and improving the photocatalytic performance of CdS. Chinese Patent (202011108636.X) uses modified nitrogen-containing defect structure graphite carbon nitride (gC3N x ) composite iron oxide (Fe2O3) to obtain a Z-type composite catalyst for photocatalytic nitrogen fixation and ammonia production. In addition, by selecting appropriate materials to prepare heterostructured photocatalysts, not only can the light absorption range be broadened, but also the separation of photogenerated electrons and holes can be promoted, thereby improving the photocatalytic performance. For example, the composite of metal oxides with different band gap widths can form new heterojunction materials such as homojunctions or heterojunctions, improve the separation of electrons and holes, form more effective electron transfer between the valence band and the conduction band, or generate more free radicals.
[0005] Microorganisms are widely present in nature, have strong growth and reproduction capabilities, and are renewable. In terms of composition, most of them contain mannan, glucan, protein (such as enzymes), lipids (mono-, di-, tri-glycerides, glycerophospholipids, sterols), DNA, carbohydrates, etc., and are good sources of carbon, nitrogen, and phosphorus. Patent 201610528866.9 uses KOH to activate yeast to prepare hierarchical porous carbon with high specific surface area, and has a good effect in adsorbing antibiotics in water.
[0006] In summary, the technical problems to be solved by the present invention are:
[0007] A method for preparing a microbially regulated and composite metal oxide photocatalytic material and its application in the photocatalytic reduction of carbon dioxide reaction are developed. The photocatalytic material prepared by this method can be used in the photocatalytic reduction of carbon dioxide reaction and has high photocatalytic performance and good stability. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing a photocatalytic material regulated by microorganisms and composite with metal oxides:
[0009] This method uses a "one-pot" green method to prepare, so that biomass-derived nitrogen and phosphorus-doped carbon materials can be directly used to modify metal semiconductor materials;
[0010] The present invention provides a method for forming heteroatom-doped carbon composite bimetallic oxides by self-assembly in a "one-pot" manner;
[0011] Furthermore, the present invention also provides an application of nitrogen-phosphorus co-doped carbon material modified metal oxide for photocatalytic reduction of carbon dioxide.
[0012] A method for preparing a photocatalytic material regulated by microorganisms and composited with metal oxides, comprising the following preparation steps:
[0013] 1) Cultivation of microorganisms
[0014] Weigh 2 to 10 parts by weight of microorganisms, add 2 to 15 parts by weight of culture medium, and let stand for 30 to 60 minutes;
[0015] 2) Preparation of microorganism-composite metal oxide gel
[0016] 10-40 mL of one or more metal salt solutions are added successively, stirred and mixed evenly, magnetically stirred at 20-70° C. for 8-15 hours, and the pH is adjusted to > 8 with an alkaline reagent to form a gel;
[0017] 3) Heat treatment to obtain the product
[0018] After a series of heat treatments and cooling, a black powder is obtained, which can be ground into nitrogen and phosphorus doped carbon material loaded with metal oxides.
[0019] As a further improvement of this solution, the microorganisms include actinomycetes, Escherichia coli, probiotics, Staphylococcus aureus, yeast, etc.
[0020] As a further improvement of this solution, the culture medium is any one or more of potato sucrose, sucrose, glucose, malt extract, and beef extract protein.
[0021] As a further improvement of this scheme, the concentration of the metal salt is 0.1 to 2 mol / L;
[0022] The metal salt is any one or more of zinc nitrate, zinc sulfate, zinc acetate, ferrous chloride, ferrous sulfate, cuprous chloride, cupric sulfate, cupric acetate, ammonium molybdate, and the like.
[0023] As a further improvement of this solution, the alkaline reagent is any one or more of ammonia water, sodium hydroxide, sodium carbonate, and sodium bicarbonate.
[0024] As a further improvement of this solution, the heat treatment method is any one or more of microwave, hydrothermal, and pyrolysis.
[0025] As a further improvement of this scheme, the following preparation steps are specifically included:
[0026] 1) Cultivation of microorganisms
[0027] Weigh 5 parts by weight of dry microorganisms, add 10 parts by weight of culture medium, and let stand for 40 minutes;
[0028] 2) Preparation of microorganism-composite metal oxide gel
[0029] 15 mL of zinc nitrate and ferrous chloride were added successively, stirred and mixed evenly, magnetically stirred at 20-70°C for 10 h, and 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel;
[0030] 3) Heat treatment to obtain the product
[0031] Put it into a microwave oven with a power of 500 W and a processing time of 3 minutes. Then add the mixture into a hydrothermal reactor and hydroheat it at 200°C for 8 hours. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral, and washed with ethanol 5 times. The obtained solid is dried in a vacuum oven at 80°C, transferred to a tubular furnace, and then heated to 750°C in a nitrogen atmosphere at a rate of 5°C / min. It is calcined for 1.5 hours and a black powder is obtained after cooling, which is the nitrogen and phosphorus doped carbon material loaded with metal oxides.
[0032] As a further improvement of this solution, the nitrogen-phosphorus doped carbon material loaded with metal oxide has a specific surface area of not less than 30 m 2 / g.
[0033] As a further improvement of the present solution, the prepared nitrogen and phosphorus doped carbon material loaded with metal oxides is applied to the photocatalytic reduction of carbon dioxide reaction.
[0034] As a further improvement of this scheme, the specific operation steps of the photocatalytic reduction of carbon dioxide reaction are as follows:
[0035] S1 weighs 0.02-0.04 parts by weight of catalyst nitrogen-phosphorus-doped carbon material loaded with metal oxide, adds 20 mL of deionized water, ultrasonically disperses for 30 minutes, evenly disperses, and then passes CO2 for 30-40 minutes.
[0036] S2 is then reacted under light for 2 to 3 hours.
[0037] Compared with the prior art, the beneficial effects of the present invention are:
[0038] The nitrogen and phosphorus co-doped carbon material described in the present invention uses microorganisms containing carbon, nitrogen and phosphorus elements as raw materials, which is low in cost and renewable;
[0039] In the preparation process of the present invention, no additional nitrogen and phosphorus sources need to be added, and the microorganisms and metal salts react in one pot to exert the regulatory effect of the microorganisms. The operation is simple and convenient, and it is suitable for large-scale production and promotion and application.
[0040] During the preparation process of the present invention, microorganisms interact with metal ions, a heterojunction is formed between the carbon material and the metal oxide, and a homojunction or heterojunction is formed between the multi-component metal oxides, which is beneficial to the separation of electrons and holes, so that electrons can be transferred and utilized more efficiently. In addition, the introduction of the carbon material increases the specific surface area of the catalyst, which is more conducive to the adsorption of substrate molecules.
[0041] The nitrogen and phosphorus co-doped carbon material composite metal oxide obtained by the method of the present invention has excellent performance and can be used for photocatalytic reduction of carbon dioxide to carbon monoxide and / or methane. It has good stability and high yield of the target product. The final CH4 yield is 1.5 μmol g -1 h -1 The CO yield was 7.3 μmol g -1 h -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a SEM image of the nitrogen and phosphorus co-doped carbon material composite zinc oxide and iron oxide prepared in Example 1.
[0043] Figure 2 This is a TEM image of the nitrogen-phosphorus co-doped carbon material composite zinc oxide and iron oxide prepared in Example 1.
[0044] Figure 3 This is the X-ray diffraction spectrum of the nitrogen and phosphorus co-doped carbon material composite zinc oxide and iron oxide prepared in Example 1.
[0045] Figure 4 This is the Raman spectrum of the nitrogen and phosphorus co-doped carbon material composite zinc oxide and iron oxide prepared in Example 1.
[0046] Figure 5 This is the nitrogen isotherm adsorption curve of the nitrogen-phosphorus co-doped carbon material composite zinc oxide and iron oxide prepared in Example 1.
[0047] Figure 6 This is the pore size distribution diagram of the nitrogen and phosphorus co-doped carbon material composite zinc oxide and iron oxide prepared in Example 1.
[0048] Figure 7 This is the EDS element mapping diagram of the nitrogen and phosphorus co-doped carbon material composite zinc oxide and iron oxide prepared in Example 1.
[0049] Figure 8 This is a comparison chart of the band gap widths of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0050] Fig. 9 These are the experimental results of the cyclic stability of the nitrogen-phosphorus co-doped carbon material composite zinc oxide and iron oxide prepared in Example 1. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described below in conjunction with the accompanying drawings and the best embodiment:
[0052] In the examples, the microorganisms are Escherichia coli unless otherwise specified, and the culture medium is beef extract protein unless otherwise specified.
[0053] Example 1
[0054] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0055] 3 g of Escherichia coli was weighed, 10 g of culture medium was added, and the mixture was allowed to stand for 40 min. 15 mL of zinc nitrate (1.2 mol / L) and ferrous chloride (1.4 mol / L) were added successively, and the mixture was stirred and mixed evenly. The mixture was stirred magnetically at 40 ° C for 10 h. 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel. The mixture was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermaled at 200 ° C for 8 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 750 ° C at a rate of 5 ° C / min in a nitrogen atmosphere. It was calcined for 1.5 h, and a black powder was obtained after cooling. The black powder was taken out and ground and sieved (100 mesh). The prepared catalyst 1 has a specific surface area of 201 m 2 / g.
[0056] 2. Application of catalyst 1 in photocatalytic carbon dioxide reduction reaction.
[0057] Weigh 0.02 g of catalyst 1, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, then pass CO2 for 30 min.
[0058] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0059] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 1.0 μmol g -1 h -1 and 6.9 μmol g -1 h -1 .
[0060] Table 1 shows the contents of various elements in the nitrogen-phosphorus co-doped carbon material composite zinc oxide and iron oxide prepared in Example 1.
[0061]
[0062] Table 2 shows the relative contents of various elements in the microorganisms of Example 1.
[0063] Element Weight % C 46 N 12 O 34 P 4 Mg 0.1 Na 0.2 K 3.3 Cl 0.4 Total 100.00
[0064] Comparative Example 1
[0065] 1. A method for preparing a microbial-regulated and composite single metal oxide photocatalytic material:
[0066] Weigh 3 g of microorganisms, add 10 g of culture medium, let stand for 40 min, add 30 mL of zinc nitrate (1.2 mol / L), stir and mix evenly, stir magnetically at 20 ° C for 10 h, use 2 mol / L ammonia water to adjust the pH to greater than 8 to form a gel, put it into a microwave oven (power 500 W) for 3 min, and then add the mixture into a hydrothermal reactor and hydroheat it at 200 ° C for 8 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tube furnace, and then heated to 750 ° C at a rate of 5 ° C / min in a nitrogen atmosphere. Calcined for 1.5 h, and a black powder was obtained after cooling. It was taken out and ground and sieved (100 mesh). The prepared catalyst 2 has a specific surface area of 110 m 2 / g.
[0067] 2. Application of catalyst 2 in photocatalytic carbon dioxide reduction reaction.
[0068] Weigh 0.02g of catalyst 2, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0μmol g -1 h -1 and 0.4 μmol g -1 h -1 .
[0069] Comparative Example 2
[0070] 1. A method for preparing a microbial-regulated and composite single metal oxide photocatalytic material:
[0071] 3 g of Escherichia coli was weighed, 10 g of culture medium was added, and the mixture was allowed to stand for 40 min. 30 mL of ferrous chloride (1.4 mol / L) was added successively, and the mixture was stirred and mixed evenly. The mixture was stirred magnetically at 40 ° C for 10 h. 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel. The mixture was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermaled at 200 ° C for 8 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tube furnace, and then heated to 750 ° C at a rate of 5 ° C / min in a nitrogen atmosphere. It was calcined for 1.5 h, and a black powder was obtained after cooling. The black powder was taken out and ground and sieved (100 mesh). The prepared catalyst 3 has a specific surface area of 126 m 2 / g. 2. Application of catalyst 3 in photocatalytic carbon dioxide reduction reaction.
[0072] Weigh 0.02g of catalyst 3, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0.7μmol g -1 h -1 and 0 μmol g -1 h -1 .
[0073] Comparative Example 3
[0074] 1. A method for preparing metal oxides:
[0075] 15 mL of zinc nitrate (1.2 mol / L) and ferrous chloride (1.4 mol / L) were added to a beaker, stirred and mixed evenly, magnetically stirred at 40°C for 10 h, and 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel, which was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermaled at 200°C for 8 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80°C, transferred to a tubular furnace, and then heated to 750°C at a rate of 5°C / min in a nitrogen atmosphere, calcined for 1.5 h, and cooled to obtain a black powder, which was taken out and ground and sieved (100 mesh). The prepared catalyst 4 contained only zinc oxide and iron oxide, with a specific surface area of 28 m 2 / g.
[0076] 2. Application of catalyst 4 in photocatalytic carbon dioxide reduction reaction.
[0077] Weigh 0.02 g of catalyst 4, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, followed by passing CO2 for 30 min.
[0078] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0079] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 0 μmol g -1 h -1 and 0.4 μmol g -1 h -1 .
[0080] The heat treatment conditions were changed based on Example 1, as shown in Comparative Examples 4-6.
[0081] Comparative Example 4
[0082] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0083] Weigh 5 g of microorganisms, add 10 g of culture medium, let stand for 40 min, add 15 mL of zinc nitrate (1.2 mol / L) and ferrous chloride (1.4 mol / L) in succession, stir and mix evenly, stir magnetically at 40 ° C for 10 h, use 2 mol / L sodium hydroxide to adjust the pH to greater than 8 to form a gel, and then add the mixture into a hydrothermal reactor and hydroheat at 200 ° C for 8 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C to obtain a black powder, which is taken out and ground and sieved (100 mesh). The prepared catalyst 5 has a specific surface area of 91 m 2 / g.
[0084] 2. Application of catalyst 5 in photocatalytic carbon dioxide reduction reaction.
[0085] Weigh 0.02g of catalyst 5, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0μmolg -1 h -1 and 0.8 μmol g -1 h -1 .
[0086] Comparative Example 5
[0087] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0088] Weigh 5 g of microorganisms, add 10 g of culture medium, let stand for 40 min, add 15 mL of zinc nitrate (1.2 mol / L) and ferrous chloride (1.4 mol / L) in succession, stir and mix evenly, stir magnetically at 50 ° C for 10 h, use 2 mol / L sodium hydroxide to adjust the pH to greater than 8 to form a gel, put it in a microwave oven (power 500 W) for 3 min, and filter the obtained solid-liquid mixture under reduced pressure. Wash it with deionized water until it is neutral. After drying the obtained solid in a vacuum oven at 80 ° C, a black powder is obtained, which is taken out and ground and sieved (100 mesh). The prepared catalyst 6 has a specific surface area of 48 m 2 / g.
[0089] 2. Application of catalyst 6 in photocatalytic carbon dioxide reduction reaction.
[0090] Weigh 0.02g of catalyst 6, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0μmol g -1 h -1 , 0.2 μmol g -1 h -1 .
[0091] Comparative Example 6
[0092] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0093] Weigh 5 g of microorganisms, add 10 g of culture medium, let stand for 40 min, add 15 mL of zinc nitrate (1.2 mol / L) and ferrous chloride (1.4 mol / L) in succession, stir and mix evenly, stir magnetically at 50 ° C for 10 h, use 2 mol / L sodium hydroxide to adjust the pH to greater than 8 to form a gel, filter under reduced pressure, and wash with deionized water to neutrality. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tube furnace, and then heated to 750 ° C at a rate of 5 ° C / min in a nitrogen atmosphere, calcined for 1.5 h, and cooled to obtain a black powder, which is taken out and ground and sieved (100 mesh). The prepared catalyst 7 has a specific surface area of 189 m 2 / g.
[0094] 2. Application of catalyst 7 in photocatalytic carbon dioxide reduction reaction.
[0095] Weigh 0.02g of catalyst 7, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0.7μmol g -1 h -1 , 5.0 μmol g -1 h -1 .
[0096] Comparative Example 7
[0097] 1. A method for preparing nitrogen and phosphorus-doped carbon materials derived from microorganisms:
[0098] Weigh 10g of microorganisms, add 15g of culture medium, stir and mix evenly, let stand for 30min, stir magnetically at 20℃ for 10h, use 3mol / L sodium hydroxide to adjust the pH to greater than 8 to form a gel, put it into a microwave oven (power 500W) for 3min, then add the mixture into a hydrothermal reactor and hydroheat it at 200℃ for 10h, the obtained solid-liquid mixture is filtered under reduced pressure, and washed with deionized water until neutral, the obtained solid is dried in a vacuum oven at 80℃, transferred to a tube furnace, and then heated to 900℃ at a rate of 10℃ / min in a nitrogen atmosphere, calcined for 2.0h, and cooled to obtain a black powder, which is taken out and ground and sieved (100 mesh). The prepared catalyst 8 has no metal oxides, and the contents of carbon, nitrogen, oxygen and phosphorus are 70%, 5%, 23% and 2% respectively (EDS elemental analysis), and the specific surface area is 300m 2 / g.
[0099] 2. Application of catalyst 8 in photocatalytic carbon dioxide reduction reaction.
[0100] Weigh 0.02g of catalyst 8, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0.0μmolg -1 h -1 and 0.0 μmol g -1 h -1 .
[0101] Table 1 Effect of heat treatment method
[0102] Heat treatment method <![CDATA[CH4 production rate (μmolg -1 h -1 )]]> <![CDATA[CO production rate (μmolg -1 h -1 )]]> Example 1 Microwave + hydrothermal + pyrolysis 1.0 6.9 Comparative Example 4 Hydrothermal 0 0.8 Comparative Example 5 microwave 0 0.2 Comparative Example 6 Pyrolysis 0.7 5.0
[0103] Example 2
[0104] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0105] 3 g of probiotics were weighed, 10 g of culture medium was added, and the mixture was allowed to stand for 40 min. 15 mL of zinc nitrate (1.2 mol / L) and ferrous chloride (1.4 mol / L) were added successively, and the mixture was stirred and mixed evenly. The mixture was stirred magnetically at 40 ° C for 10 h. 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel. The mixture was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermally heated at 200 ° C for 8 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 600 ° C at a rate of 5 ° C / min in a nitrogen atmosphere. The powder was calcined for 2 h, and a black powder was obtained after cooling. The powder was taken out and ground and sieved (100 mesh). The prepared catalyst 9 had a specific surface area of 178 m 2 / g.
[0106] 2. Application of catalyst 9 in photocatalytic carbon dioxide reduction reaction.
[0107] Weigh 0.02 g of catalyst 9, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, then pass CO2 for 30 min.
[0108] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0109] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.8 μmol g -1 h -1 and 6.1 μmol g -1 h -1 .
[0110] Example 3
[0111] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0112] 3 g of probiotics were weighed, 10 g of culture medium was added, and the mixture was allowed to stand for 40 min. 15 mL of zinc nitrate (1.2 mol / L) and ferrous chloride (1.4 mol / L) were added successively, the mixture was stirred and mixed evenly, magnetically stirred at 40 ° C for 10 h, 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel, which was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermaled at 200 ° C for 8 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 750 ° C at a rate of 5 ° C / min in a nitrogen atmosphere, calcined for 2 h, and a black powder was obtained after cooling. The black powder was taken out and ground and sieved (100 mesh). The prepared catalyst 10 had a specific surface area of 200 m 2 / g.
[0113] 2. Application of catalyst 10 in photocatalytic carbon dioxide reduction reaction.
[0114] Weigh 0.02 g of catalyst 10, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, then pass CO2 for 30 min.
[0115] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0116] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 1.0 μmol g -1 h -1 and 6.8 μmol g -1 h -1 .
[0117] Example 4
[0118] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0119] 3 g of probiotics were weighed, 10 g of culture medium was added, and the mixture was allowed to stand for 40 min. 15 mL of zinc nitrate (1.2 mol / L) and ferrous chloride (1.4 mol / L) were added successively, the mixture was stirred and mixed evenly, magnetically stirred at 40 ° C for 10 h, 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel, which was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermaled at 200 ° C for 8 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 900 ° C at a rate of 5 ° C / min in a nitrogen atmosphere, calcined for 2 h, and a black powder was obtained after cooling. The powder was taken out and ground and sieved (100 mesh). The prepared catalyst 11 had a specific surface area of 215 m 2 / g.
[0120] 2. Application of catalyst 11 in photocatalytic carbon dioxide reduction reaction.
[0121] Weigh 0.02 g of catalyst 11, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, then pass CO2 for 30 min.
[0122] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0123] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.9 μmol g -1 h -1 and 6.5 μmol g -1 h -1 .
[0124] Example 5
[0125] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0126] 3 g of probiotics were weighed, 10 g of culture medium was added, and the mixture was allowed to stand for 40 min. 15 mL of zinc nitrate (1.2 mol / L) and ferrous chloride (1.4 mol / L) were added successively, and the mixture was stirred to mix evenly. The mixture was stirred magnetically at 40 ° C for 10 h. 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel. The gel was placed in a microwave oven (power 500 W) for 3 min, and the mixture was added to a hydrothermal reactor and hydrothermally heated at 200 ° C for 8 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 750 ° C at a rate of 5 ° C / min in an argon atmosphere. The powder was calcined for 2 h, and a black powder was obtained after cooling. The powder was taken out and ground and sieved (100 mesh). The prepared catalyst 12 had a specific surface area of 198 m 2 / g.
[0127] 2. Application of catalyst 12 in photocatalytic carbon dioxide reduction reaction.
[0128] Weigh 0.02 g of catalyst 12, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, followed by passing CO2 for 30 min.
[0129] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0130] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 0.5 μmol g -1 h -1 and 4.7 μmol g -1 h -1 .
[0131] Table 2 Effect of pyrolysis conditions
[0132]
[0133] Example 6
[0134] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0135] Weigh 5 g of yeast, add 12 g of culture medium, let stand for 40 min, add 15 mL of zinc nitrate (0.8 mol / L) and ferrous chloride (1.0 mol / L) in succession, stir and mix evenly, stir magnetically at 40 ° C for 10 h, adjust the pH to greater than 8 with 2 mol / L ammonia water to form a gel, put it in a microwave oven (power 500 W) for 3 min, and then add the mixture into a hydrothermal reactor and hydroheat it at 180 ° C for 8 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 750 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcined for 2 h, and cooled to obtain a black powder. The powder is taken out and ground and sieved (100 mesh). The prepared catalyst 13 has a specific surface area of 190 m 2 / g.
[0136] 2. Application of catalyst 13 in photocatalytic carbon dioxide reduction reaction.
[0137] 0.02 g of catalyst 13 was weighed, added with 20 mL of deionized water, and ultrasonically dispersed for 30 min to achieve uniform dispersion, followed by passing CO2 for 30 min.
[0138] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0139] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.9 μmol g -1 h -1 and 6.5 μmol g -1 h -1 .
[0140] Example 7
[0141] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0142] Weigh 5 g of yeast, add 12 g of culture medium, let stand for 40 min, add 15 mL of zinc nitrate (0.8 mol / L) and ferrous chloride (1.0 mol / L) in succession, stir and mix evenly, stir magnetically at 40 ° C for 10 h, adjust the pH to greater than 8 with 1 mol / L ammonia water to form a gel, put it in a microwave oven (power 500 W) for 3 min, and then add the mixture into a hydrothermal reactor and hydroheat it at 180 ° C for 8 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 750 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcined for 2 h, and cooled to obtain a black powder. Take it out and grind and sieve (100 mesh). The prepared catalyst 13 has a specific surface area of 190 m 2 / g.
[0143] 2. Application of catalyst 13 in photocatalytic carbon dioxide reduction reaction.
[0144] 0.02 g of catalyst 13 was weighed, added with 20 mL of deionized water, and ultrasonically dispersed for 30 min to achieve uniform dispersion, followed by passing CO2 for 30 min.
[0145] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0146] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.8 μmol g -1 h -1 and 6.4 μmol g -1 h -1 .
[0147] Example 8
[0148] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0149] Weigh 5 g of yeast, add 12 g of culture medium, let stand for 40 min, add 15 mL of zinc nitrate (0.8 mol / L) and ferrous chloride (1.0 mol / L) in succession, stir and mix evenly, stir magnetically at 40 ° C for 10 h, adjust the pH to greater than 8 with 3 mol / L ammonia water to form a gel, put it in a microwave oven (power 500 W) for 3 min, and then add the mixture into a hydrothermal reactor and hydroheat it at 180 ° C for 8 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 750 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcined for 2 h, and cooled to obtain a black powder. The powder is taken out and ground and sieved (100 mesh). The prepared catalyst 14 has a specific surface area of 190 m 2 / g.
[0150] 2. Application of catalyst 14 in photocatalytic carbon dioxide reduction reaction.
[0151] 0.02 g of catalyst 14 was weighed, added with 20 mL of deionized water, and ultrasonically dispersed for 30 min to achieve uniform dispersion, followed by passing CO2 for 30 min.
[0152] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0153] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 0.5 μmol g -1 h -1 and 6.3 μmol g -1 h -1 .
[0154] Example 9
[0155] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0156] Weigh 5g of yeast, add 12g of culture medium, let it stand for 40min, add 15mL of zinc nitrate (0.8mol / L) and ferrous chloride (1.0mol / L) in succession, stir and mix evenly, stir magnetically at 40℃ for 10h, adjust the pH to greater than 8 with 2mol / L sodium hydroxide aqueous solution to form a gel, put it into a microwave oven (power 500W) for 3min, and then add the mixture into a hydrothermal reactor and hydroheat it at 180℃ for 8h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80℃, transferred to a tubular furnace, and then heated to 750℃ at a rate of 10℃ / min in a nitrogen atmosphere, calcined for 2h, and cooled to obtain a black powder. The powder is taken out and ground and sieved (100 mesh). The prepared catalyst 13 has a specific surface area of 150m2 / g.
[0157] 2. Application of catalyst 13 in photocatalytic carbon dioxide reduction reaction.
[0158] 0.02 g of catalyst 13 was weighed, added with 20 mL of deionized water, and ultrasonically dispersed for 30 min to achieve uniform dispersion, followed by passing CO2 for 30 min.
[0159] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0160] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.7 μmol g -1 h -1 and 6.3 μmol g -1 h -1 .
[0161] Example 10
[0162] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0163] Weigh 5 g of yeast, add 12 g of culture medium, let stand for 40 min, add 15 mL of zinc nitrate (0.8 mol / L) and ferrous chloride (1.0 mol / L) in succession, stir and mix evenly, stir magnetically at 40 ° C for 10 h, use 2 mol / L sodium carbonate aqueous solution to adjust the pH to greater than 8 to form a gel, put it into a microwave oven (power 500 W) for 3 min, and then add the mixture into a hydrothermal reactor and hydroheat it at 180 ° C for 8 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 750 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcined for 2 h, and a black powder is obtained after cooling. The black powder is taken out and ground and sieved (100 mesh). The prepared catalyst 14 has a specific surface area of 140 m 2 / g.
[0164] 2. Application of catalyst 14 in photocatalytic carbon dioxide reduction reaction.
[0165] 0.02 g of catalyst 14 was weighed, added with 20 mL of deionized water, and ultrasonically dispersed for 30 min to achieve uniform dispersion, followed by passing CO2 for 30 min.
[0166] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0167] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.6 μmol g -1 h -1 and 6.2 μmol g -1 h -1 .
[0168] Embodiment 11
[0169] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0170] Weigh 5 g of yeast, add 12 g of culture medium, let stand for 40 min, add 15 mL of zinc nitrate (0.8 mol / L) and ferrous chloride (1.0 mol / L) in succession, stir and mix evenly, stir magnetically at 40 ° C for 10 h, use 2 mol / L sodium bicarbonate aqueous solution to adjust the pH to greater than 8 to form a gel, put it into a microwave oven (power 500 W) for 3 min, and then add the mixture into a hydrothermal reactor and hydroheat it at 180 ° C for 8 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tube furnace, and then heated to 750 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcined for 2 h, and cooled to obtain a black powder. Take it out and grind and sieve (100 mesh). The prepared catalyst 15 has a specific surface area of 193 m 2 / g.
[0171] 2. Application of catalyst 15 in photocatalytic carbon dioxide reduction reaction.
[0172] 0.02 g of catalyst 15 was weighed, added with 20 mL of deionized water, and ultrasonically dispersed for 30 min to achieve uniform dispersion, followed by passing CO2 for 30 min.
[0173] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0174] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.6 μmol g -1 h -1 and 6.2 μmol g -1 h -1 .
[0175] Table 3 Effect of alkali type and concentration
[0176] Alkali (concentration) <![CDATA[CH4 production rate (μmol g -1 h -1 )]]> <![CDATA[CO production rate (μmolg -1 h -1 )]]> Example 6 Ammonia (2M) 0.8 6.9 Example 7 Ammonia (1M) 0.7 6.4 Example 8 Ammonia (3M) 0.5 6.3 Example 9 Sodium hydroxide (2M) 0.7 6.3 Example 10 Sodium carbonate (2M) 0.6 6.2 Embodiment 11 Sodium bicarbonate (2M) 0.6 6.2
[0177] Example 12
[0178] 1. Cycling experiment of catalyst 1 in photocatalytic carbon dioxide reduction reaction.
[0179] The catalyst from Example 1 was recovered, washed several times with 20 mL of ethanol and 20 mL of deionized water, and dried in a vacuum oven. The photocatalytic carbon dioxide reduction reaction of Example 1 was then cycled. After four cycles, the CH4 or CO yield was calculated. The CH4 and CO production rates were 1.0 μmol g -1 h -1 and 6.8 μmol g -1 h-1 (like Fig. 9 shown).
[0180] The effects of different bacteria on catalyst preparation are as follows:
[0181] Embodiment 13
[0182] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0183] 5 g of Escherichia coli was weighed, 10 g of culture medium was added, and the mixture was allowed to stand for 40 min. 15 mL of zinc acetate (0.5 mol / L) and ferrous sulfate (2.0 mol / L) were added successively, and the mixture was stirred to be uniform. The mixture was stirred magnetically at 40 ° C for 10 h. 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel. The mixture was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermally heated at 180 ° C for 10 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 800 ° C at a rate of 5 ° C / min in a nitrogen atmosphere. It was calcined for 1.5 h, and a black powder was obtained after cooling. The black powder was taken out and ground and sieved (100 mesh). The prepared catalyst 16 had a specific surface area of 195 m 2 / g.
[0184] 2. Application of catalyst 16 in photocatalytic carbon dioxide reduction reaction.
[0185] Weigh 0.02 g of catalyst 16, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, followed by passing CO2 for 30 min.
[0186] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0187] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.6 μmol g -1 h -1 and 5.8 μmol g -1 h -1 .
[0188] Embodiment 14
[0189] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0190] Weigh 5 g of yeast, add 10 g of culture medium, let stand for 40 min, add 15 mL of zinc acetate (0.5 mol / L) and ferrous sulfate (2.0 mol / L) in succession, stir and mix evenly, stir magnetically at 40 ° C for 10 h, adjust the pH to greater than 8 with 2 mol / L ammonia water to form a gel, put it into a microwave oven (power 500 W) for 3 min, and then add the mixture into a hydrothermal reactor and hydroheat it at 180 ° C for 10 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 800 ° C at a rate of 5 ° C / min in a nitrogen atmosphere, calcined for 1.5 h, and cooled to obtain a black powder. Take it out and grind and sieve (100 mesh). The prepared catalyst 17 has a specific surface area of 200 m 2 / g.
[0191] 2. Application of catalyst 17 in photocatalytic carbon dioxide reduction reaction.
[0192] Weigh 0.02 g of catalyst 17, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, followed by passing CO2 for 30 min.
[0193] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0194] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 0.5 μmol g -1 h -1 and 5.4 μmol g -1 h -1 .
[0195] Embodiment 15
[0196] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0197] 5 g of probiotics were weighed, 10 g of culture medium was added, and the mixture was allowed to stand for 40 min. 15 mL of zinc acetate (0.5 mol / L) and ferrous sulfate (2.0 mol / L) were added successively, the mixture was stirred and mixed evenly, magnetically stirred at 40 ° C for 10 h, 2 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel, which was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydroheated at 180 ° C for 10 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 800 ° C at a rate of 5 ° C / min in a nitrogen atmosphere, calcined for 1.5 h, and a black powder was obtained after cooling. The black powder was taken out and ground and sieved (100 mesh). The prepared catalyst 18 had a specific surface area of 200 m 2 / g.
[0198] 2. Application of catalyst 18 in photocatalytic carbon dioxide reduction reaction.
[0199] Weigh 0.02 g of catalyst 18, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, then pass CO2 for 30 min.
[0200] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0201] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 0.5 μmol g -1 h -1 and 5.3 μmol g -1 h -1 .
[0202] Table 4 Effects of different microorganisms
[0203] microorganism <![CDATA[CH4 production rate (μmol g -1 h -1 )]]> <![CDATA[CO production rate (μmolg -1 h -1 )]]> Embodiment 13 Escherichia coli 0.6 5.8 Embodiment 14 Yeast 0.5 5.4 Embodiment 15 Probiotics 0.5 5.3 Comparative Example 7 / 0 0
[0204] Examples of other metal salts used to prepare microbial regulation and composite single / multi-metal oxide photocatalytic materials are as follows:
[0205] Example 16
[0206] 1. A method for preparing a microbial-regulated and composite metal oxide photocatalytic material:
[0207] Weigh 5 g of microorganisms, add 10 g of culture medium, let stand for 40 min, add 15 mL of zinc sulfate (0.2 mol / L) and cuprous chloride (1.5 mol / L) in succession, stir and mix evenly, stir magnetically at 30 ° C for 13 h, adjust the pH to greater than 8 with 3 mol / L ammonia water to form a green gel, put it into a microwave oven (power 500 W) for 5 min, then add the mixture into a hydrothermal reactor and hydroheat it at 180 ° C for 9 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 800 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcined for 2 h, and cooled to obtain a black powder. Take it out and grind and sieve (100 mesh). The prepared catalyst 19 has a specific surface area of 110 m 2 / g.
[0208] 2. Application of catalyst 19 in photocatalytic carbon dioxide reduction reaction.
[0209] Weigh 0.02g of catalyst 19, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), and calculate the CH4 or CO yield. The CH4 and CO production rates are 0.9μmol g -1 h -1 and 5.7 μmol g -1 h -1 .
[0210] Embodiment 17
[0211] 1. Weigh 5g of microorganisms, add 10g of culture medium, let stand for 40min, add 15mL of cuprous chloride (1.5mol / L), stir and mix evenly, stir magnetically at 30℃ for 13h, adjust the pH to greater than 8 with 3mol / L ammonia water to form a green gel, put it in a microwave oven (power 500W) for 5min, then add the mixture into a hydrothermal reactor and hydrothermally heat it at 180℃ for 9h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80℃, transferred to a tube furnace, and then heated to 750℃ at a rate of 10℃ / min in a nitrogen atmosphere, calcined for 2h, and cooled to obtain a black powder, which is taken out and ground and sieved (100 mesh). The prepared catalyst 20 has a specific surface area of 115m 2 / g.
[0212] 2. Application of catalyst 20 in photocatalytic carbon dioxide reduction reaction.
[0213] Weigh 0.02g of catalyst 20, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0.2μmolg -1 h -1 and 1.7 μmol g -1 h -1 .
[0214] Embodiment 18
[0215] 1. A method for preparing a microbial-regulated and composite metal oxide photocatalytic material:
[0216] Weigh 5 g of microorganisms, add 10 g of culture medium, let stand for 40 min, add 15 mL of zinc acetate (0.3 mol / L) and ammonium molybdate (1.6 mol / L) in succession, stir and mix evenly, stir magnetically at 60 ° C for 13 h, use 3 mol / L sodium bicarbonate to adjust the pH to greater than 8 to form a gel, put it into a microwave oven (power 500 W) for 4 min, and then add the mixture into a hydrothermal reactor and hydroheat it at 180 ° C for 10 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 700 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcined for 2 h, and cooled to obtain a black powder. Take it out and grind and sieve (100 mesh). The prepared catalyst 21 has a specific surface area of 145 m 2 / g.
[0217] 2. Application of catalyst 21 in photocatalytic carbon dioxide reduction reaction.
[0218] Weigh 0.02g of catalyst 21, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0μmol g -1 h -1 and 6.4 μmol g -1 h -1 .
[0219] Embodiment 19
[0220] 1. A method for preparing a microbial-regulated and composite metal oxide photocatalytic material:
[0221] Weigh 5 g of microorganisms, add 10 g of culture medium, let stand for 40 min, add 15 mL of ammonium molybdate solution (1.6 mol / L), stir and mix evenly, stir magnetically at 60 ° C for 13 h, use 3 mol / L sodium bicarbonate to adjust the pH to greater than 8 to form a gel, put it into a microwave oven (power 500 W) for 4 min, and then add the mixture into a hydrothermal reactor and hydroheat it at 180 ° C for 10 h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80 ° C, transferred to a tube furnace, and then heated to 800 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcined for 2 h, and a black powder is obtained after cooling. It is taken out and ground and sieved (100 mesh). The prepared catalyst 22 has a specific surface area of 160 m 2 / g.
[0222] 2. Application of catalyst 22 in photocatalytic carbon dioxide reduction reaction.
[0223] Weigh 0.02g of catalyst 22, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0μmolg -1 h -1 and 1.2 μmol g -1 h -1 .
[0224] Embodiment 20
[0225] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0226] 5 g of staphylococcus was weighed, 12 g of culture medium was added, and the mixture was allowed to stand for 40 min. 15 mL of ferrous sulfate (0.8 mol / L) and copper acetate (1.5 mol / L) were added successively, the mixture was stirred and mixed evenly, magnetically stirred at 50 ° C for 10 h, and the pH value was adjusted to greater than 8 with 2 mol / L sodium carbonate to form a gel. The mixture was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermal at 180 ° C for 9 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 700 ° C at a rate of 7 ° C / min in a nitrogen atmosphere. It was calcined for 2 h, and a black powder was obtained after cooling. The black powder was taken out and ground and sieved (100 mesh). The prepared catalyst 23 has a specific surface area of 150 m 2 / g.
[0227] 2. Application of catalyst 23 in photocatalytic carbon dioxide reduction reaction.
[0228] Weigh 0.02g of catalyst 23, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 1.4μmol g -1 h -1 and 7.1 μmol g -1 h -1 .
[0229] Embodiment 21
[0230] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0231] 8 g of staphylococcus was weighed, 14 g of culture medium was added, and the mixture was allowed to stand for 30 min. 15 mL of ferrous chloride (1.2 mol / L) and ammonium molybdate (1.0 mol / L) were added successively, and the mixture was stirred and mixed evenly. The mixture was stirred magnetically at 40 ° C for 10 h. The pH value was adjusted to greater than 8 with 2 mol / L ammonia water to form a gel. The mixture was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermally heated at 180 ° C for 10 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tubular furnace, and then heated to 600 ° C at a rate of 5 ° C / min in a nitrogen atmosphere. It was calcined for 2.0 h, and a black powder was obtained after cooling. The black powder was taken out and ground and sieved (100 mesh). The prepared catalyst 24 had a specific surface area of 130 m 2 / g.
[0232] 2. Application of catalyst 24 in photocatalytic carbon dioxide reduction reaction.
[0233] Weigh 0.02g of catalyst 24, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 1.2μmolg -1 h -1 and 1.0 μmol g -1 h -1 .
[0234] Embodiment 22
[0235] 1. A method for preparing a microbial-regulated and composite bimetallic oxide photocatalytic material:
[0236] Weigh 3g of yeast, add 12g of culture medium, let stand for 50min, add 15mL of cuprous chloride (2.0mol / L) and ammonium molybdate (1.2mol / L) in succession, stir and mix evenly, stir magnetically at 25℃ for 10h, adjust the pH value to greater than 8 with 2mol / L ammonia water to form a gel, put it in a microwave oven (power 500W) for 3min, then add the mixture into a hydrothermal reactor and hydroheat it at 180℃ for 10h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80℃, transferred to a tubular furnace, and then heated to 650℃ at a rate of 5℃ / min in a nitrogen atmosphere, calcined for 2.0h, and a black powder is obtained after cooling. The powder is taken out and ground and sieved (100 mesh). The prepared catalyst 25 has a specific surface area of 80m 2 / g.
[0237] 2. Application of catalyst 25 in photocatalytic carbon dioxide reduction reaction.
[0238] Weigh 0.02g of catalyst 25, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0.6μmolg -1 h -1 and 4.8 μmol g -1 h -1 .
[0239] Embodiment 23
[0240] 1. A method for preparing a microbial-regulated and composite metal oxide photocatalytic material:
[0241] 5 g of microorganisms were weighed, 15 g of culture medium was added, and the mixture was allowed to stand for 40 min. 10 mL of zinc sulfate (0.8 mol / L), ferrous chloride (1.0 mol / L) and cuprous chloride (0.9 mol / L) were added successively, and the mixture was stirred and mixed evenly. The mixture was stirred magnetically at 50 ° C for 13 h. 3 mol / L ammonia water was used to adjust the pH to greater than 8 to form a gel. The mixture was placed in a microwave oven (power 500 W) for 5 min, and then the mixture was added to a hydrothermal reactor and hydrothermally heated at 180 ° C for 9 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 ° C, transferred to a tube furnace, and then heated to 750 ° C at a rate of 5 ° C / min in a nitrogen atmosphere. It was calcined for 2 h, and a black powder was obtained after cooling. The black powder was taken out and ground and sieved (100 mesh). The prepared catalyst 26 had a specific surface area of 120 m 2 / g.
[0242] 2. Application of catalyst 26 in photocatalytic carbon dioxide reduction reaction.
[0243] Weigh 0.02g of catalyst 26, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 1.1μmol g -1 h -1 1 and 7.4 μmol g -1 h -1 .
[0244] Embodiment 24
[0245] 1. A method for preparing a microbial-regulated and composite metal oxide photocatalytic material:
[0246] 6 g of microorganisms were weighed, 15 g of culture medium was added, and the mixture was allowed to stand for 40 min. 10 mL of zinc acetate (0.5 mol / L), ferrous chloride (0.8 mol / L) and ammonium molybdate (0.7 mol / L) were added successively, and the mixture was stirred and mixed evenly. The mixture was stirred magnetically at 40 °C for 15 h. 2 mol / L sodium hydroxide was used to adjust the pH to greater than 8 to form a gel. The mixture was placed in a microwave oven (power 500 W) for 3 min, and then the mixture was added to a hydrothermal reactor and hydrothermaled at 200 °C for 9 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 °C, transferred to a tubular furnace, and then heated to 800 °C at a rate of 5 °C / min in a nitrogen atmosphere. The mixture was calcined for 1.5 h. After cooling, a black powder was obtained. The powder was taken out and ground and sieved (100 mesh). The prepared catalyst 27 had a specific surface area of 100 m2 / g.
[0247] 2. Application of catalyst 27 in photocatalytic carbon dioxide reduction reaction.
[0248] Weigh 0.02g of catalyst 27, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 0.7μmolg -1 h -1 and 7.3 μmol g -1 h -1 .
[0249] Embodiment 25
[0250] 1. A method for preparing a microbial-regulated and composite multi-metal oxide photocatalytic material:
[0251] Weigh 10g of microorganisms, add 15g of culture medium, let stand for 40min, add 10mL of ferrous sulfate (0.5mol / L), copper sulfate (1.2mol / L) and ammonium molybdate (0.3mol / L) in succession, stir and mix evenly, stir magnetically at 35℃ for 13h, adjust the pH to greater than 8 with 2mol / L ammonia water to form a green gel, put it into a microwave oven (power 500W) for 5min, then add the mixture into a hydrothermal reactor and hydroheat at 180℃ for 9h. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral. The obtained solid is dried in a vacuum oven at 80℃, transferred to a tubular furnace, and then heated to 700℃ at a rate of 5℃ / min in a nitrogen atmosphere, calcined for 2h, and cooled to obtain a black powder, which is taken out and ground and sieved (100 mesh). The prepared catalyst 28 has a specific surface area of 60m 2 / g,.
[0252] 2. Application of catalyst 28 in photocatalytic carbon dioxide reduction reaction.
[0253] Weigh 0.02g of catalyst 28, add 20mL of deionized water, and disperse evenly by ultrasonic dispersion for 30min, then pass CO2 for 30min. Then react for 2h under light (300W xenon lamp simulates sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph (GC-14C), calculate the CH4 or CO yield, and the CH4 and CO production rates are 1.0μmol g -1 h -1 and 7.1 μmol g-1 h -1 .
[0254] Embodiment 26
[0255] 1. A method for preparing a microbial-regulated and composite multi-metal oxide photocatalytic material:
[0256] 10 g of microorganisms were weighed, 15 g of culture medium was added, and the mixture was allowed to stand for 40 min. 7.5 mL of zinc sulfate (0.2 mol / L), ferrous chloride (1.2 mol / L), cuprous chloride (0.9 mol / L) and ammonium molybdate (0.3 mol / L) were added successively and mixed evenly. The mixture was stirred magnetically at 35 °C for 15 h. 3 mol / L ammonia water was used to adjust the pH to greater than 8 to form a green gel. The gel was placed in a microwave oven (power 500 W) for 5 min. The mixture was then added to a hydrothermal reactor and hydrothermally heated at 180 °C for 9 h. The obtained solid-liquid mixture was filtered under reduced pressure and washed with deionized water until neutral. The obtained solid was dried in a vacuum oven at 80 °C, transferred to a tubular furnace, and then heated to 750 °C at a rate of 5 °C / min in a nitrogen atmosphere. The powder was calcined for 2 h. After cooling, a black powder was obtained. The powder was taken out and ground and sieved (100 mesh). The prepared catalyst 29 had a specific surface area of 96 m 2 / g.
[0257] 2. Application of catalyst 29 in photocatalytic carbon dioxide reduction reaction.
[0258] Weigh 0.02 g of catalyst 29, add 20 mL of deionized water, and disperse evenly by ultrasonic dispersion for 30 min, followed by passing CO2 for 30 min.
[0259] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0260] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 1.5 μmol g -1 h -1 and 7.3 μmol g -1 h -1 .
[0261] Embodiment 27
[0262] 1. Cycling experiment of catalyst 29 in photocatalytic carbon dioxide reduction reaction.
[0263] The catalyst from Example 26 was recovered, washed several times with 20 mL of ethanol and 20 mL of deionized water, dried in a vacuum oven, and then cycled according to the photocatalytic carbon dioxide reduction reaction of Example 1. After four cycles, the CH4 or CO yield was calculated. The CH4 and CO production rates were 1.4 μmol g -1 h -1 and 7.3 μmol g -1 h -1 .
[0264] Table 5 Effect of the type and ratio of metal salts
[0265]
[0266]
[0267] It can be seen from the above examples and comparative examples that in the present invention, by mixing metal salts, preferably mixing zinc sulfate / ferrous chloride / cuprous chloride / ammonium molybdate, the final CH4 yield is 1.5 μmol g -1 h -1 The CO yield was 7.3 μmol g -1 h -1 .
[0268] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent changes made using the present invention are within the patent protection scope of the present invention.
Claims
1. A method for preparing a photocatalytic material regulated by microorganisms and composite with metal oxides, characterized in that: The method comprises the following preparation steps: 1) Cultivation of microorganisms Weigh 2 to 10 parts by weight of microorganisms, add 2 to 15 parts by weight of culture medium, and let stand for 30 to 60 minutes; 2) Preparation of microorganism-composite metal oxide gel 10-40 mL of one or more metal salt solutions are added successively, stirred and mixed evenly, magnetically stirred at 20-70° C. for 8-15 hours, and the pH is adjusted to > 8 with an alkaline reagent to form a gel; 3) Heat treatment to obtain the product After a series of heat treatments, black powder is obtained after cooling, and grinding is nitrogen and phosphorus doped carbon material loaded with metal oxides; The concentration of the metal salt is 0.1 to 2 mol / L; The metal salt is any combination of zinc nitrate / ferrous chloride, zinc sulfate / cuprous chloride, ferrous sulfate / cuprous acetate, ferrous chloride / ammonium molybdate, cuprous chloride / ammonium molybdate, zinc sulfate / ferrous chloride / cuprous chloride, zinc acetate / ferrous chloride / ammonium molybdate, ferrous sulfate / cuprous sulfate / ammonium molybdate, zinc sulfate / ferrous chloride / cuprous chloride / ammonium molybdate; The heat treatment method is microwave, hydrothermal, and pyrolysis.
2. The method for preparing a photocatalytic material controlled by microorganisms and composited with metal oxides according to claim 1, characterized in that: The microorganisms include any one or more of actinomycetes, Escherichia coli, probiotics, Staphylococcus aureus, and yeast.
3. The method for preparing a photocatalytic material controlled by microorganisms and composited with metal oxides according to claim 1, characterized in that: The culture medium is any one or more of potato sucrose, sucrose, glucose, malt extract and beef extract protein.
4. The method for preparing a photocatalytic material controlled by microorganisms and composited with metal oxides according to claim 1, characterized in that: The alkaline reagent is any one or more of ammonia water, sodium hydroxide, sodium carbonate and sodium bicarbonate.
5. The method for preparing a photocatalytic material controlled by microorganisms and composited with metal oxides according to claim 1, characterized in that: Specifically comprising the following preparation steps: 1) Cultivation of microorganisms Weigh 5 parts by weight of dry microorganisms, add 10 parts by weight of culture medium, and let stand for 40 minutes; 2) Preparation of microorganism-composite metal oxide gel 15 mL of zinc nitrate and ferrous chloride were added successively, and the mixture was stirred evenly. The mixture was stirred magnetically at 20-70°C for 10 h, and the pH was adjusted to be greater than 8 with 2 mol / L ammonia water to form a gel; 3) Heat treatment to obtain the product Put it into a microwave oven with a power of 500 W and a processing time of 3 minutes. Then add the mixture into a hydrothermal reactor and hydroheat it at 200°C for 8 hours. The obtained solid-liquid mixture is filtered under reduced pressure and washed with deionized water until neutral, and washed with ethanol 5 times. The obtained solid is dried in a vacuum oven at 80°C, transferred to a tubular furnace, and then heated to 750°C in a nitrogen atmosphere at a rate of 5°C / min. It is calcined for 1.5 hours and a black powder is obtained after cooling, which is the nitrogen and phosphorus doped carbon material loaded with metal oxides.
6. The method for preparing a photocatalytic material controlled by microorganisms and composited with metal oxides according to any one of claims 1 to 5, characterized in that: The specific surface area of the metal oxide loaded by the nitrogen and phosphorus doped carbon material is not less than 30m 2 / g.
7. The method for preparing a photocatalytic material controlled by microorganisms and composited with metal oxides according to any one of claims 1 to 5, characterized in that: The prepared nitrogen and phosphorus doped carbon material loaded with metal oxide is applied to the photocatalytic reduction of carbon dioxide reaction.
8. The method for preparing a photocatalytic material controlled by microorganisms and composited with metal oxides according to claim 7, characterized in that: The specific operation steps of the photocatalytic reduction of carbon dioxide reaction are as follows: S1 weighed 0.02-0.04 parts by weight of catalyst nitrogen and phosphorus doped carbon material loaded with metal oxide, added 20 mL of deionized water, ultrasonically dispersed for 30 minutes, uniformly dispersed, and then passed CO2 for 30-40 minutes; S2 is then reacted under light for 2 to 3 hours.
Citation Information
Patent Citations
Preparation method and application of saccharomycetes-based hierarchical porous carbon material
CN106185922A
Preparation methods and applications of nitrogen-containing defective Z-type carbon nitride-iron oxide catalysts
CN112371146B
Stable ternary composite material for hydrogen production by photocatalytic decomposition of water and preparation method thereof
CN112892607A
Preparation and application of acid-resistant octahedral porous nitrogen-phosphorus-doped carbon-coated iron oxide nano material
CN117563649A